Are Small Adrenal Incidentalomas Solely a Radiological Finding? - Eroglu, M.; Erbag, G.; Turkon, H.; Binnetoglu, E.; Ozkul, F.; Gunes, F.; Sen, H.; Yilmaz, Y.; Sahin, M.; Ukinc, K.; Asik, M. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: The criterium defining the threshold size of adrenal incidentaloma (AI) is a size greater than 1 cm diameter. However, data concerning AI≤1 cm in diameter is scant. The aim of this study was to evaluate the function of adrenal masses≤1 cm and to compare them with adrenal masses>1 cm.Materials and Methods: The study included 130 consecutive patients with AI (38 and 92 AI at ≤ 1 cm and > 1 cm, respectively). The patients were evaluated according to demographic and hormonal characteristics.Results: The prevalence of SCS was 5.3 and 12% in AI≤1 cm and > 1 cm diameter, respectively. Hyperaldosteronism was found only in patients with > 1 cm AI. Pheochromocytoma were not found in either group. Patients with > 1 cm AI had a higher prevalence of SCS and primary hyperaldosteronism than patients with ≤ 1 cm AI, but the difference was not significant. The prevalence of diabetes and hypertension was high both in non-functional AI with ≤ 1 cm and > 1 cm patients and showed no significant difference between the 2 groups.Conclusion: Our study is the first to focus on the clinical and hormonal characteristics of patients with ≤ 1 cm AI. Those with AI≤1 cm harboured SCS, as was the case for AI>1 cm. Similar to AI>1 cm, non-functional AI≤1 cm also had a higher prevalence of diabetes and hypertension.
Keywords: adrenal incidentaloma; subclinical Cushing’s syndrome; adrenal size